Изменчивость окраски и рисунка в двух отдаленных популяциях цикадки Macropsis prasina (Воh., 1852) (Homoptera, Cicadellidae) - Хохлова, С.Ю.; Ануфриева, Г.А. (Вестник зоологии, 1981)
The paper deals with a description of colour and pattern variability in Macropsis prasina (В о h.) from Gorky and Lithuanian populations. Phenograms of various populations which reflect the ratios of the phene frequencies in development of certaip pattern spots are of the same type, which permits them to be considered as a good species criterion for the Macropsis L e w . genus polymorphous species. With similar phene phene frequencies the frequencies of certain pattern phenotypes in the compared populations differ considerably. A dark-wing variety (var. fuscipennis, var. nov.) occurs among males of the Gorky population, which differs greatly from light-wing males of the same and other populations in the pattern phenotype frequency ratio. A possibility to separate visually numerous colour and pattern phenotypes in the Macropsis representatives inhabiting willows makes them a good object for population studies.